Development of Technique for Producing Decorative Bamboo Veneer from Indian Sympodial Bamboo - Uday, D. N.; Singh, M. P.; Mamatha, B. S.; Prakash, V.; Sujatha, D.; Anand, N. (Indian Forester, 2024)
Decorative panel industry in the country is currently facing tough situation of severe shortage of decorative face veneers. The present study focusses on to find out alternate methods of making face veneers by utilizing Indian sympodial bamboo to meet the challenges posed by the shortage of face quality veneers as it is very much necessary for continuing the production of panel in the industry without disruption. Bambusa tulda and Bambusa nutans were used for the study. Melamine formaldehyde (MF) resin was used for making Glulam of size 1000 mm(l) x 120 mm(w) x 180 mm(t). Bamboo veneer of 0.3 mm thick were developed using these flitches. The decorative bamboo veneer were matched to a size of 1000 mm x 1000 mm and overlaid on Plywood panels to produce decorative panels. The resulting Bamboo veneer is a consistent in colour and pattern. Testing's were carried out on overlaid plywood as per specifications for veneered decorative plywood. It has been observed that the quality of veneer produced is satisfactory and meets requirements as per IS: 1328 – 1996 and can be used for producing sliced bamboo decorative veneers.